Physical activity domains and risk of gastric adenocarcinoma in the MCC-Spain case-control study - Huerta, José M.; Chirlaque, María Dolores; Molina, Antonio J.; Amiano, Pilar; Martín, Vicente; Fernández-Villa, Tania; Pérez-Gómez, Beatriz; Moreno, Víctor; Burgui, Rosana; Gómez-Acebo, Inés; Ramos-Lora, Manuel; Fernández-Tardón, Guillermo; et al. (PLOS ONE, 2017)
Background Evidence for a protective role of physical activity against development of stomach cancer is yet inconclusive. We studied the association of domain-specific physical activity and the risk of gastric adenocarcinoma (GAC), by site and histology, in the MCC-Spain case-control study. Methods 428 histologically confirmed GAC cases (67% men) including the gastro-esophageal region and 3225 controls were included. Cases were recruited in hospitals from 10 different Spanish regions, whereas population controls were randomly selected within the respective hospitals' catchment areas. A physical activity (PA) questionnaire was used to gather information on household and recreational activities, allowing estimation of PA volume (in metabolic equivalents (MET)-min/week). Participants also reported the intensity of working PA and daily sitting time. Questionnaire data on diet, lifestyles and clinical variables including Helicobacter pylori serology were available. Adjusted odds ratios (OR) of GAC were estimated for domains of physical activity, stratifying by sex, site (cardia vs. non-cardia), and Lauren classification (intestinal vs. diffuse). Results Household physical activity (HPA) showed a strong inverse association with GAC, observed for both cardia and non-cardia tumours. Risk of overall gastric cancer was 50% lower risk among participants in the highest HPA category (OR = 0.50, 95%CI: 0.38, 0.66). Recreational physical activity (RPA) was also associated with lower overall GAC risk (OR = 0.68, 95% CI: 0.52, 0.88), particularly at moderate levels of intensity such as walking (OR = 0.61, 95% CI: 0.46, 0.79). The protective effect of RPA was strongest for non-cardia tumours. Sedentary time was not related to GAC risk (p-trend = 0.392), but the potential protective effect of RPA was restricted to non-sedentary participants. Conclusions Both household and recreational physical activities were independently related to lower GAC risk in the MCC-Spain study.